Finger island flaps for treatment of dermato-desmogenic flexion contractures of proximal interphalangeal joints - T. S. Antonova; D. V. Іvchenko (Zaporozhye State Medical University, 2016)
Soft tissue defect will form after operative treatment of the dermato-desmogenic flexion contractures of fingers interphalangeal joints of the 2-3 grades after excision of the scar. Using the island flaps (Littler) at the central vascular pedicle is one of the classical methods of plastic closure of such defects. Goal. To study the effectiveness of the surgical treatment of dermato-desmogenic flexion contractures of proximal interphalangeal joints of the fingers by using finger island flaps at the central vascular or neuro-vascular pedicle. Materials and methods. 14 operations were carried out on 13 patients for removing dermato-desmogenic flexion contractures of proximal interphalangeal (PIP) joints of triphalangeal fingers over a 2-year period (2013-2015). The group included patients with a flexion contracture of the 2-3 grades PIP joints of triphalangeal fingers. Operations were performed on average 5 months after the injury (from 1.5 up to 16 months). Finger island flap in all cases was taken from adjacent finger by using the blood supply of their common finger artery. In all cases the island flap on the central pedicel was used, in 9 cases digital nerve was included in the pedicle (Littler). Closure of donor wound was made with free-skin grafts. Permanent splinting of the hand with extension of the interphalangeal joints and moderate flexion of the metacarpophalangeal joints were performed during 7-8 days after surgery, then exercise therapy was prescribed. Results. The results were estimated 6 and 12 months after surgery. All the results were regarded as excellent. In 5 cases of using the flap on a vascular pedicle flap hypoesthesia was detected, that has not led to dysfunction of the hand. Contracture recurrence during follow-up was not observed. Conclusions. Using the surgery for treatment of dermato-desmogenic flexion contractures of proximal interphalangeal joints of the fingers with the island flaps at the central vascular or neuro-vascular pedicle allows to achieve good functional and aesthetic results.